Optimization of 3D-printed modular living walls in hot arid regions - Carol Victor George Ayad; Samah El Khateeb; Noha Gamal Said; Wesam M. Elbardisy (Ain Shams Engineering Journal, 2025)
Urban walls have transformed into barriers providing an opportunity for vertical modular living walls as presented by growing literature. Industry 4.0 additive manufacturing was employed to facilitate design customization. This study targets application-based optimization of 3D-printed modular vessels for hot arid regions through a mixed-method approach by combining a five-day workshop and experiment-driven optimization for minimized 3D printing time and waste. The results indicated key factors for optimization including geometry selection, and iterative development. Despite minor fabrication errors, the improved model reduced 30–80 % of the support waste aligning with 15–65 % achieved by previous studies, which diminished printing time by up to 5–10 h compared to the workshop model. These findings provide valuable insights for urban and landscape designers into the potential of repurposing urban walls into living walls. The study presents a novel approach through integrating computational optimization using 3D printing, with real-world evaluation for effective vertical greening.